30 de ani de apropiere de Hasdeu: B.P. Hasdeu. Scrieri. Vol. 1-21, Ed. Știința (1993-2023) - UNGUREANU, Elena (BIBLIOPOLIS, 2025)
The editorial project “B.P. Hasdeu. Writings” (21 volumes, 1993-2023), published through a partnership between the B.P. Hasdeu Municipal Library and Știința Publishing House, represents a landmark achievement, unique in the Romanian cultural space. Initially conceived as a 16-volume series, the project was expanded to reflect the complexity of Hasdeu’s work as poet, prose writer, playwright, historian, linguist, journalist, and folklorist. The series offers an encyclopedic synthesis of his contributions in multiple fields: literature, linguistics, and national history. The extensive critical apparatus and introductory studies enhance the academic value of the edition. Through this collection, Hasdeu is affirmed as a foundational figure of Romanian culture.